An Analysis of Code-Mixing in Presentations by English Department Students of Universitas Kuningan - Nabila, Salsa; Syarafina, Zatalini Nadhilah; Ardianti, Vania Putri; Darsih, Endang (Proceedings Series on Social Sciences & Humanities, 2025)
Code-mixing or language mixing is often found in bilingual contexts, especially in academic activities such as student presentations. This research is motivated by the use of code-mixing by sixth-semester students of the English Education Study Program of Universitas Kuningan in the presentation of Sociolinguistics in the ELT course. The purpose of this study is to identify the factors that encourage the use of code-mixing, analyze the pattern of code-mixing used, and evaluate its impact on the clarity of the message in the presentation. The method used was descriptive qualitative, with data collection techniques through observation, presentation transcripts, and interviews. The results showed that there were three types of code-mixing used, namely: inner code-mixing at 3.5% (3 utterances), outer code-mixing at 39.5% (34 utterances), and hybrid code-mixing as the most dominant at 57% (49 utterances) of the total 86 utterances analyzed. The five main factors driving the use of code-mixing are audience understanding, spontaneity of speaking, emphasizing important points, self-confidence, and limited vocabulary.